2020
DOI: 10.3390/jpm11010004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ageing Protein β-Klotho Rejuvenates Diabetic Stem Cells for Improved Gene-Activated Scaffold Based Wound Healing

Abstract: Skin wounds can lead to serious morbidity complications in diabetic patients due to the reduced healing potential of autologous stem cells. One reason for the low functional potency of stem cells from diabetic patients (diabetic stem cells) is attributed to their senescent-like nature. Here, we investigated if an anti-ageing protein, β-klotho, could be used to rejuvenate diabetic stem cells and to promote pro-angiogenic gene-activated scaffold (GAS)-induced functional response for wound healing applications. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Enhancement of angiogenesis in subdermal tissues is detected in these studies ( 49 , 76 ). ASCs can also be delivered by gene-activated scaffold, in which typical gene related to wound healing process is facilitated ( 52 , 80 ). Laiva et al.…”
Section: Clinical Progress Of Ascs In Treating Diabetic Woundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancement of angiogenesis in subdermal tissues is detected in these studies ( 49 , 76 ). ASCs can also be delivered by gene-activated scaffold, in which typical gene related to wound healing process is facilitated ( 52 , 80 ). Laiva et al.…”
Section: Clinical Progress Of Ascs In Treating Diabetic Woundsmentioning
confidence: 99%
“…Suku et al. investigated β-klotho gene-activated scaffold to reduce the release of interleukin-8 to suppress inflammatory process ( 80 ). In addition, gene-modified scaffolds may be more targeted to specific pathological conditions.…”
Section: Clinical Progress Of Ascs In Treating Diabetic Woundsmentioning
confidence: 99%
“…16.480700 doi: bioRxiv preprint and improve its low mechanical strength. Natural polymers are preferred over synthetic polymers because of their outstanding biodegradability and biocompatibility (22) (23).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical cross-linking or combined hybridization with synthetic polymers or natural polysaccharides are considered effective methodologies for manufacturing superior CLG-based scaffolds to minimize the possibility of CLG degradation and improve its low mechanical strength. Natural polymers are preferred over synthetic polymers because of their outstanding biodegradability and biocompatibility (22) (23). Numerous co- and synthetic polymers have been employed in conjunction with CLG.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ADSCs tend to lose their stemness upon expansion [31]. Previously, we found that an anti-aging protein β-Klotho could significantly improve the proliferation of healthy and diabetic human ADSCs [32]. Most studies generally use the primary variant α-Klotho [33][34][35] and have shown that the protein can increase the lifespan of ADSCs by activating the telomerase transcriptional activity [33].…”
Section: Introductionmentioning
confidence: 99%